Tone of earnings announcements in sin industries. Issue 2 (7th May 2019) - Luo, Yan; Zhou, Linying
Abstract : Purpose: The purpose of this paper is to investigate the empirical association between the tone of earnings announcements and a company's membership in a sin industry. Design/methodology/approach: This study constructs a model of the determinants of earnings announcement tone to examine the impact of sin industry membership on earnings announcement tone. An interaction term between CEO power (CEO–chairman duality) and sin industry membership is used to test whether CEO power moderates the strength of the association. The earnings announcements tone is measured using the spread in the proportion of positive and negative words. The category of sin industry includes not only industries such as tobacco, gambling and alcohol, but also industries associated with emerging environmental, social, and ethical issues (i.e. firearms, oil and cement). Findings: The analysis of a sample of US firms from the 1994 to 2013 period shows that the tone of earnings announcement is less optimistic for companies in sin industries, but this association is weaker for companies that are led by powerful CEOs. The results remain robust to alternative definitions of sin industry membership and CEO power (CEO tenure) and to alternative model specifications. Originality/value: The findings suggest that although sin companies cannot change the nature of their business, the management of such companies, in general, uses a less aggressive tone in their earnings announcements. These results further investors' understanding of sin companies' reporting behavior.